To expand 1/3 (q - 6) using the distributive property, you need to multiply 1/3 by both terms inside the parentheses:
1/3 * q = q/3
1/3 * -6 = -6/3 = -2
Therefore, the expanded form is q/3 - 2, which is equivalent to answer choice D. 1/3q - 2.
Expand 1/3 (q - 6) using distributive property. (1 Point)
A. -1/3 q+2
B. 1/3 q - 6
C. -1/3 q +6
D. 1/3q - 2
5 answers
Expand 2/5 (-5c + 10). (1 point)
A. -2c + 10
B. 2c - 10
C. 2c - 4
D. -2c + 4
A. -2c + 10
B. 2c - 10
C. 2c - 4
D. -2c + 4
To expand 2/5 (-5c + 10) using the distributive property, you need to multiply 2/5 by both terms inside the parentheses:
2/5 * -5c = -10c/5 = -2c
2/5 * 10 = 20/5 = 4
Therefore, the expanded form is -2c + 4, which is equivalent to answer choice D. -2c + 4.
2/5 * -5c = -10c/5 = -2c
2/5 * 10 = 20/5 = 4
Therefore, the expanded form is -2c + 4, which is equivalent to answer choice D. -2c + 4.
Expand -7/6 (3g + 2). (1 point)
A. 7/2g + 2
B. -7/2g -7/3
C. 7/2g - 7/3
D. -7/2g + 2
A. 7/2g + 2
B. -7/2g -7/3
C. 7/2g - 7/3
D. -7/2g + 2
To expand -7/6 (3g + 2) using the distributive property, you need to multiply -7/6 by both terms inside the parentheses:
-7/6 * 3g = -21g/6 = -7/2g
-7/6 * 2 = -14/6 = -7/3
Therefore, the expanded form is -7/2g - 7/3, which is equivalent to answer choice B. -7/2g - 7/3.
-7/6 * 3g = -21g/6 = -7/2g
-7/6 * 2 = -14/6 = -7/3
Therefore, the expanded form is -7/2g - 7/3, which is equivalent to answer choice B. -7/2g - 7/3.